Ovum-Pick Up and In Vitro Embryo Production Responses in Stimulated and Non-Stimulated Sahiwal Cows - Chandra, Pradeep; Kumar, Brijesh; Donadkar, Manoj M; rathi, Bhagi; Jasrotia, Nancy; Chouhan, Vikrant Singh; Kharayat, Nitish Singh; Singh, Sanjay Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The aim of the present study was to evaluate follicular population, oocyte recovery, quality, and in vitro embryo developmental  competence in non-stimulated and FSH stimulated Sahiwal cows subjected to ovum pick-up (OPU) and in vitro embryo production  (IVEP). The study was conducted on total 16 cows divided into two groups; group 1 FSH stimulated (n=08) and group 2 non-stimulated  (n=08) Sahiwal cows. A total of 16 OPU sessions were performed in early luteal phase of estrous cycles. The mean number of follicles  aspirated (17.13±1.87 Vs. 12.38±0.85) and the mean number of oocytes recovered (10.25±0.98 Vs. 6.75±0.60) per OPU per animal were  significantly (p
Keywords: Embryo; FSH; OPU-IVF; Quality; Sahiwal cows